Problematika Upah Minimum Kota/Kabupaten (UMK) sebagai Dasar Perhitungan Iuran BPJS Kesehatan bagi Pekerja Penerima Upah Swasta - Abdi, Nanang; Saleh, Moh. (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
The research began with the problem of the city/district minimum wage as a basis for calculating health insurance contributions, where there are still several regions that overlap with each other, where the minimum wage difference is large and there are still employers who have not registered workers in the health insurance program. The research method uses a normative juridical research type with a statutory approach and a case approach. The results of the discussion are that the system for calculating BPJS contributions according to the UMK is still regulated in Presidential Decree 59/2024, where there is potential for social inequality and efforts to resolve the calculation of health insurance contributions in the form of making a collective agreement between workers, employers and elements of trade unions regarding adjustments to the amount of wages linked to payment capacity. health insurance contributions.